2020
DOI: 10.1002/slct.201903937
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid as an Efficient Organocatalyst for the Synthesis of 2‐Substituted‐2,3‐dihydroquinazolin‐4(1H)‐one and 2‐Substituted Quinazolin‐4(3H)‐one in Water

Abstract: An environmentally benign, robust and straightforward protocol has been developed for the synthesis of a diverse array of 2,3‐dihydroquinazolin‐4(1H)‐ones using 2‐aminobenzamide and various aldehydes or ketones. Water, a green solvent was adopted in this methodology replacing hazardous reaction mediums. Further, ascorbic acid, an organocatalyst has been accepted to meet the role of catalyst, thus bypassing the use of noxious metals or hazardous materials, which is another asset of this protocol. The activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 60 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Erfan et al [38] reported a highly efficient synthetic route using SBA‐16/GPTMS‐TSC‐CuI solvent‐free protocols, which provided an impressive yield of 98% in 20 min. Pariyar et al [39] used ascorbic acid at 90°C in H 2 O to give 92% quinazoline in 1 h. Maleki et al [40] used nano‐Fe 3 O 4 @GO under reflux in EtOH and yielded 80% in 3 h. Sharma et al [41] achieved a DHQ using cyanuric chloride at room temperature in CH 3 CN with a yield of 96% in 10 min. The methods show some common drawbacks such as expensive catalysts, tedious catalyst separation procedures, use of hazardous solvents, acidic reaction conditions, longer reaction time, non‐selectivity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Erfan et al [38] reported a highly efficient synthetic route using SBA‐16/GPTMS‐TSC‐CuI solvent‐free protocols, which provided an impressive yield of 98% in 20 min. Pariyar et al [39] used ascorbic acid at 90°C in H 2 O to give 92% quinazoline in 1 h. Maleki et al [40] used nano‐Fe 3 O 4 @GO under reflux in EtOH and yielded 80% in 3 h. Sharma et al [41] achieved a DHQ using cyanuric chloride at room temperature in CH 3 CN with a yield of 96% in 10 min. The methods show some common drawbacks such as expensive catalysts, tedious catalyst separation procedures, use of hazardous solvents, acidic reaction conditions, longer reaction time, non‐selectivity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include NH 4 Cl" [17] I 2 , [18] [Bmim] PF 6 , [13d] cellulose-SO 3 H, [3] NaHSO 4 , [19] cyanuric chloride, [20] HScellulose sulfonate, [21] morpholinoethanesulfonic acid, [22] trifluoroethanol, [23] citrus extract modified graphene oxide [24] and ascorbic acid. [25] However, a majority of synthetic methods still require expensive/hazardous catalysts, harmful solvents, long reaction times, and high temperatures. In addition, the prerequisite for some of these methods are tedious reaction quenching steps.…”
Section: Introductionmentioning
confidence: 99%